2015
DOI: 10.1111/geb.12360
|View full text |Cite
|
Sign up to set email alerts
|

A global synthesis of the effects of biological invasions on greenhouse gas emissions

Abstract: Aim Evidence is mounting that biological invasions profoundly alter the capacity of ecosystems to regulate or mitigate greenhouse gas (GHG) emissions – a crucial ecosystem service in a changing climate. However, the growing literature has revealed different, even contradictory results and the general pattern over large spatial scales remains obscure. This study synthesizes the effects of invasions by different alien taxa on major GHG emissions. Location Global. Methods A structured meta‐analysis of 68 case stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…; Pejchar & Mooney ; Vilà et al. ; Qiu ). If we are to address the effects of invasive species, we need to understand their establishment, dynamics, and relationship with invaded ecosystems.…”
mentioning
confidence: 99%
“…; Pejchar & Mooney ; Vilà et al. ; Qiu ). If we are to address the effects of invasive species, we need to understand their establishment, dynamics, and relationship with invaded ecosystems.…”
mentioning
confidence: 99%
“…and nitrogen fixation Qiu, 2015); -Loss of land for cattle due to dense vegetation van Wilgen and Leisure and recreation EDS:…”
Section: Safety and Securitymentioning
confidence: 99%
“…In this respect, meta-analyses employing quantitative methods are conceivably more objective than review articles, because they should be less susceptible to preconceived notions. Although some meta-analyses concluded that the impacts of NIS are stronger and/ or more detrimental than those of indigenous species (Ferlian et al, 2018;Paolucci, MacIsaac, & Ricciardi, 2013;Salo, Korpimaki, Banks, Nordstrom, & Dickman, 2007;Simberloff, Souza, Nuñez, Barrios-Garcia, & Bunn, 2012;van Hengstum, Hooftman, Oostermeijer, Tienderen, & Mack, 2014;Vilá et al, 2011;Wood et al, 2017;Yoon & Read, 2016), many suggested positive influences and/or that the purported negative effects of NIS are not supported by evidence (Charlebois, Sargent, & Maherali, 2017;Gurevitch & Padilla, 2004;Norkko et al, 2011;Pintor, Byers, & Anderson, 2015;Radville, Gonda-King, Gómez, Kaplan, & Preisser Evan, 2014;Reise, Olenin, & Thieltges, 2006), and most found variable and context-dependent impacts (Cameron, Vilà, Cabeza, & Sykes, 2016;Guy-Haim et al, 2018;Higgins & Vander Zanden, 2010;Howard, Therriault, & Côté, 2017;Martin, Newton, & Bullock, 2017;Nelson et al, 2017;Potgieter et al, 2017;Pysek et al, 2008;Qiu, 2015;Thomsen et al, 2014;Twardochleb, Olden, & Larson, 2013;Vaz et al, 2018;Ward & Ricciardi, 2007), thus hindering broad generalizations.…”
Section: Interpre Ting and Recon Ciling D Iss Entmentioning
confidence: 99%